2017
DOI: 10.1007/s40436-017-0200-y
|View full text |Cite
|
Sign up to set email alerts
|

The fit of Industry 4.0 applications in manufacturing logistics: a multiple case study

Abstract: The fourth industrial revolution, Industry 4.0, is expected to cause disruptive changes in industrial production. It is driven by rapid technological developments and the need for manufacturing companies to make oneself independent of high labor costs. Industry 4.0 concerns several aspects of industrial production, including manufacturing logistics, business models and products and services. The applications of Industry 4.0 have been vastly outlined. However, the fit of Industry 4.0 applications in different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(106 citation statements)
references
References 35 publications
2
100
0
4
Order By: Relevance
“…Similarly, for Industry 4.0, it is argued that environmental factors will have a significant impact on the applicability of Industry 4.0. Through a multiple case study, Strandhagen et al (2017) find that companies with repetitive production systems on a general basis should have an easier transition to Industry 4.0 than non-repetitive production systems. Other researchers claim that only big enterprises will be able to reap the benefits from Industry 4.0 and that small and medium-sized enterprises (SMEs) can quickly become the victims of Industry 4.0 (Sommer 2015).…”
Section: Linking Industry 40 and Lean Manufacturingmentioning
confidence: 99%
“…Similarly, for Industry 4.0, it is argued that environmental factors will have a significant impact on the applicability of Industry 4.0. Through a multiple case study, Strandhagen et al (2017) find that companies with repetitive production systems on a general basis should have an easier transition to Industry 4.0 than non-repetitive production systems. Other researchers claim that only big enterprises will be able to reap the benefits from Industry 4.0 and that small and medium-sized enterprises (SMEs) can quickly become the victims of Industry 4.0 (Sommer 2015).…”
Section: Linking Industry 40 and Lean Manufacturingmentioning
confidence: 99%
“…Starting from the German strategic initiative, Industry 4.0 is presently a major frame of a few countries from the U.S., Europe, and Asia (Kagermann et al 2013;Ślusarczyk 2018). It has worked quickly in the creation of advanced ideas (Strandhagen et al 2017); for instance, the Internet of things (IoT), big data, smart factory, cyber physical systems, and interoperability rely upon a prompt change in the outlook in mechanical creation. Nowadays, most production and services companies are moving towards higher technology by introducing Industry 4.0 ideas (Oláh et al 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Various applications for industrial 4.0 technology in manufacturing logistics have been identi ied and placed in four groups, namely decision support and decision-making; identi ication and interconnectivity; seamless information low; and automation, robots & new production technology (Strandhagen, et al, 2017), as shown in Table 1 below.…”
Section: Application Of Industry 40 In Value Chainmentioning
confidence: 99%